Explorating Sound and Pronunciation Errors in Bahasa Indonesia by Foreign Content Creators in Social Media - Putu Desi Anggerina Hikmaharyanti (Suar Betang, 2025)
This study explores the mispronunciation of Indonesian phonemes by non-native speakers, especially content creators on TikTok, highlighting the research gap between formal language training and actual practice on social media. While previous studies have addressed second language phonology acquisition in general, few have examined the context of digital content and its practical implications. This study uses a qualitative approach with observation and analysis techniques of videos uploaded by foreign creators on TikTok. The data was collected from a sample of videos covering a variety of topics and content created by foreign speakers with various native language backgrounds. The results showed a variety of pronunciation and sound errors made by the foreign speakers in using Indonesian. These errors include the pronunciation of nasal sound /ŋ/ in term of consonant and vowels /e/ /ə/ that do not comply with Indonesian pronunciation standards. Factors that influence these pronunciation and sound errors include phonological differences between the foreign speakers' mother tongue and Indonesian, moreover there was too much generalization due to lack of understanding of Indonesian phonetic rules. By understanding the common mistakes, more effective learning strategies can be designed such as minimal pairs /e/-/ə/ and audiovisual-based interactive /ŋ/ sound spectrograms comprehension.